School Counselor's Understanding of Professional Counselor Ethics and Competence at SMA Negeri 10 Medan - Anggi Dwi Noperlis; Yeni Karneli; Rezki Hariko (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
Professional ethics and competence of professional guidance and counseling counselors is a very important part of his life and work as a guidance and counseling teacher (counselor). The purpose of this research is to find out about the understanding of school counselors about the ethics and competence of professional counselors. This research method is a qualitative phenomenology in which to get accurate information directly to the counseling teacher by conducting observations and interviews. the objects in this study were 2 (two) counseling guidance teachers. the result of his research is that school counselors must have ethics and competence as the foundation of their profession. Professional counselors need to have a strong desire and determination to help others and have the positive attitude to see their clients as people with different values, religious teachings, cultures, and backgrounds. Counselors must have full responsibility, self-control and emotional stability, and be fully aware of differences in values, religions, cultures and beliefs. _____________________________________________________________ Etika profesi dan kompetensi konselor bimbingan dan konseling profesional merupakan bagian yang sangat penting dalam kehidupan dan pekerjaannya sebagai seorang guru bimbingan dan konseling (konselor). Tujuan dari penelitian ini adalah untuk mengetahui tentang pemahaman konselor sekolah tentang etika dan kompetensi konselor profesional. Metode penelitian ini adalah kualitatif fenomenologi dimana untuk mendapatkan informasi yang akurat langsung kepada guru bimbingan konseling dengan melakukan observasi dan wawancara. objek dalam penelitian ini adalah 2 (dua) orang guru bimbingan konseling. hasil penelitiannya adalah konselor sekolah harus memiliki etika dan kompetensi sebagai landasan profesinya. Konselor profesional perlu memiliki keinginan dan tekad yang kuat untuk membantu orang lain dan memiliki sifat positif untuk melihat kliennya sebagai orang yang berbeda nilai, ajaran agama, budaya, dan latar belakang. Konselor harus memiliki tanggung jawab penuh, pengendalian diri dan kestabilan emosi, serta menyadari sepenuhnya perbedaan nilai, agama, budaya dan kepercayaan.